The Eficiency in The Management of Facial Fracture Patients in Developing Country by Using OsiriX®, A Free 3D-Rendering Software - Kreshanti, Prasetyanugraheni; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Being a developing country with a GNI (Gross National Income) per capita of US3,830, the cost for managing patients with facial fractures was often unaffordable. The use of a free 3D-rendering software presumably would decrease cost. With OsiriX, a free and open source 3D-rendering software, complex images manipulations and real-time 3D image visualization is easily accessible anytime and anywhere from the surgeon’s personal computer, making diagnosis and preoperative planning more convenient for the surgeons. Patients and methods: From December 2009 to January 2010, 14 patients with facial fracture were admitted to our unit. Seven of them underwent surgery. Preoperatively, diagnosis & surgery plan was developed using OsiriX. Results: By using OsiriX, more accurate diagnosis was made at a lower cost. Patients could save up to 48.1% from total diagnostic cost (19.2% from monthly income). OsiriX provided easier access to multidimensional navigation and visualization tools in personal computers, making easier planning possible for surgical steps and materials needed. Summary: OsiriX being free and open source is bene!cial from !nancial point of view, which is an important point for patients in a developing country. It is user friendly and ef!cient in developing treatment plan for facial fracture patients.